2020
DOI: 10.1021/acs.biomac.0c00818
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Methods to Characterize the Mechanical Response of Soft Biomaterials

Abstract: Raman spectroscopy has been used extensively to characterize the influence of mechanical deformation on microstructure changes in biomaterials. While traditional piezo-spectroscopy has been successful in assessing internal stresses of hard biomaterials by tracking prominent peak shifts, peak shifts due to applied loads are near or below the resolution limit of the spectrometer for soft biomaterials with moduli in the kilo- to mega-Pascal range. In this Review, in addition to peak shifts, other spectral feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Hence, it could result in a smaller percentage of alpha and triple helix in hCol with a certain amount of type III collagen as seen in Figure 3C and D . For other regions, although the Raman positions of peaks in C–C, C–S stretching region, amide III and C–H bending position were different to some degree between bCol I and hCol, it could attributed to spectral variability and broad spectral features in biological samples [ 59 , 60 ]. For fibrillar structure, SEM and TEM showed a 68-nm D-periodicity of collagen fibril in hCol.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it could result in a smaller percentage of alpha and triple helix in hCol with a certain amount of type III collagen as seen in Figure 3C and D . For other regions, although the Raman positions of peaks in C–C, C–S stretching region, amide III and C–H bending position were different to some degree between bCol I and hCol, it could attributed to spectral variability and broad spectral features in biological samples [ 59 , 60 ]. For fibrillar structure, SEM and TEM showed a 68-nm D-periodicity of collagen fibril in hCol.…”
Section: Discussionmentioning
confidence: 99%
“…The L a values are 18.2, 11.2, 9.6, 15.6, 14.0, and 13.7 nm for the different graphene oxides (from S-1 to S-6), and these values are lesser than the L a of graphite (122 nm). These results indicated that there is no linear relation to quantify the amounts of sp 3 and sp 2 domains present in graphene oxide with different oxidation degrees. Altogether, the Raman analysis showed the occurrence crystalline to amorphous transition with disruption of stacking order when graphite is oxidized into graphene oxide.…”
Section: Raman Spectral Studies Of Graphene Oxide With Various Levels Of Oxidationmentioning
confidence: 93%
“…Raman spectroscopy is a promising non-destructive testing of materials to understand their crystallinity, chemical bonding vibrations and effects of surface defects [1,2]. The Raman spectroscopy becomes an important technique for the characterization of nanostructured materials, especially the two-dimensional (2D) materials (such as graphene, MoS 2 , siloxene, metalenes), biomaterials, composites, and for understanding energy-conversion process in the recent years [3][4][5]. Additionally, these techniques are useful for criminological & forensic applications, biomedical applications, and as well as bio-sensors for health care sectors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Polarized Raman spectroscopy (PRS) can overcome the above limitation because it can detect alignment at the molecular level as it is based on vibrational light-scattering technique in which the intensity of the signal relies on the orientation of vibrating molecules relative to the laser polarization direction . Hence, PRS can extract structural information not only about collagen but all other biomacromolecules, such as multiple proteins and other cell components . Since PRS can be performed in aqueous environments, it holds a distinct advantage over polarized Fourier-transform infrared spectroscopy in probing highly hydrated tissue samples .…”
Section: Introductionmentioning
confidence: 99%
“…14 Hence, PRS can extract structural information not only about collagen but all other biomacromolecules, such as multiple proteins and other cell components. 15 Since PRS can be performed in aqueous environments, it holds a distinct advantage over polarized Fourier-transform infrared spectroscopy in probing highly hydrated tissue samples. 16 In our own 17 and other studies, 18−20 PRS has been used to characterize the organization of matrix in native tissue.…”
Section: ■ Introductionmentioning
confidence: 99%